Tindak Pidana Korupsi Yang Dilakukan oleh Perempuan - Nussy, Jennifer Ingelyne; Latumaerissa, Denny (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2024)
Introduction: Women today commit many crimes. Crimes committed by women are very detrimental to themselves and even the country. The crime committed by women is corruption. Corruption committed by women is caused by factors, so that women enter the circle of corruption. Purposes of the Research: This article aims to find out corruption crimes committed by women. Methods of the Research: This paper uses the method of statutory approach (statute approach) and conceptual approach (conceptual approach). Results of the Research: Corruption is a form of crime that often occurs and is not only known at the national level, but also internationall. The view that corruption has become a very big threat to the country and has even caused the country to decline. Corruption crimes today are not only committed by men, but women are starting to aggressively commit corruption crimes. Corruption committed by women is considered bad behavior and tarnishes oneself and even the family itself. Basically, crimes committed by women are things that are driven by the desire to be rich and even live a luxurious life, wrong relationships, lack of salary, abuse of position or position, influence of the environment in which one lives and even lack of understanding of religion. This is a factor for women to commit corruption crimes. For this reason, serious countermeasures are needed to suppress corruption crimes committed by women so that in the future women will no longer commit acts of corruption.